Pengaruh Kinerja Keuangan, Komite Audit dan Prudence terhadap Nilai Perusahaan : Studi Empiris Sektor Consumer Non Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Maslina Maslina; Andry Sugeng (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Firm value is an important indicator for investors in assessing a company’s performance and future prospects. In recent years, fluctuations in firm value within the consumer non-cyclicals sector in Indonesia have attracted attention, particularly in relation to financial performance, corporate governance mechanisms, and the application of accounting prudence. This study aims to analyze the determinants of firm value by examining financial performance, audit committee characteristics, and prudence as influencing factors. The research employs a quantitative approach using secondary data obtained from companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange during the period 2020–2024. The population consists of all firms in the sector, with a final sample of 21 companies selected, resulting in 105 firm-year financial statement observations. Descriptive statistical analysis and multiple regression analysis are applied to test the proposed hypotheses. The data are processed using EViews version 12. The results indicate that financial performance, audit committee, and prudence simultaneously have a significant effect on firm value. However, partial testing shows that financial performance does not have a significant effect on firm value, while the audit committee has a significant positive effect. Prudence, on the other hand, does not significantly influence firm value. These findings suggest that corporate governance, particularly the role of the audit committee, plays a more critical role in enhancing firm value than financial performance and accounting prudence in the observed sector.